Knowledge About Dengue Fever Prevention Among People Visiting Benazir Bhutto Hospita - Tamanna Fayyaz , Maria Yasin , Ahsan Tariq , Aashi Mughal , Mujtaba Haider Bukhari , Khushbakht, Tamanna Fayyaz , Maria Yasin , Ahsan Tariq , Aashi Mughal , Mujtaba Haider Bukhari , Khushbakht (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: The higher incidence of dengue fever in Pakistan demands additional efforts in order to limit the disease. Despite active public health campaigns, low public awareness is one of the factors facilitating dengue virus transmission. For effective preventive measures, the assessment of the knowledge gap and then taking appropriate steps to fill the gap is required. The objective of this study is to assess knowledge about dengue fever prevention among people visiting Benazir Bhutto Hospital, Rawalpindi. Material and Methods: The descriptive cross-sectional study of 6 months duration was conducted with 280 participants selected via nonprobability convenience sampling. After informed consent, an interview was conducted based on a questionnaire that assessed socio-demographic parameters and knowledge about dengue virus transmission and prevention. Data were analyzed through SPSS v.22. The study was approved by the Ethical Review Board (ERB) of Rawalpindi Medical University and Allied hospitals. Results: Out of 280 respondents, 54.6% were males and 45.4% females and the mean age was 35.0 ± 13.1 years. The respondents having high knowledge scores were 66(23.6%) while those having moderate and low scores were 159 (56.8%) and 55 (19.6%) respectively. Educated respondents (p=0.03) and urban residents (p=0.05) had higher knowledge scores. Conclusion: Majority of the participants know about dengue fever. However, only one out of every four respondents have good knowledge scores for dengue fever prevention. Keywords: Dengue Virus, Mosquito bite, Dengue fever.